2002
DOI: 10.1002/esp.341
|View full text |Cite
|
Sign up to set email alerts
|

Impact–entrainment relationship in a saltating cloud

Abstract: The problem of impact-entrainment relationship is one of the central issues in understanding saltation, a primary aeolian transport mode. By using particle dynamic analyser measurement technology the movement of saltating particles at the very near-surface level (1 mm above the bed) was detected. The impacting and entrained particles in the same impact-entrainment process were identified and the speeds, angle with respect to the horizontal, and energy of the impacting and entrained sand cloud were analysed. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
86
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 46 publications
12
86
6
Order By: Relevance
“…Nalpanis et al (1993) found that the probability distributions of resultant lift-off velocity and angle are similar to a log-normal distribution. The experiment of Dong et al (2002a) described the velocity distribution of entrained particles as a Weibull function, the probability of resultant lift-off velocity decreases with increasing resultant lift-off velocity, but the probability distribution of lift-off angles is complex and cannot be expressed by a simple function. In the numerical model of Namikas (2003), both gamma and exponential launch velocity distributions are studied.…”
Section: The Distribution Of Resultant Lift-off Velocity and Angle Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Nalpanis et al (1993) found that the probability distributions of resultant lift-off velocity and angle are similar to a log-normal distribution. The experiment of Dong et al (2002a) described the velocity distribution of entrained particles as a Weibull function, the probability of resultant lift-off velocity decreases with increasing resultant lift-off velocity, but the probability distribution of lift-off angles is complex and cannot be expressed by a simple function. In the numerical model of Namikas (2003), both gamma and exponential launch velocity distributions are studied.…”
Section: The Distribution Of Resultant Lift-off Velocity and Angle Ofmentioning
confidence: 99%
“…White and Schulz, 1977;Willetts and Rice, 1986;Anderson and Hallet, 1986;Werner and Haff, 1988;Anderson and Haff, 1988;Sørensen, 1991;Haff and Anderson, 1993;Nalpanis et al, 1993;Rice et al, 1995Rice et al, , 1996Dong et al, 2002a;Namikas, 2003). If the probability distributions of the horizontal and vertical lift-off velocities or the resultant lift-off velocity and angle of saltating grains are known, the proportion of the number of grains with a given resultant lift-off velocity and lift-off angle will be acquired, then the macroscopic statistic of particles can be deduced from the representative trajectories of saltating grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willetts and Rice, 1986;Anderson and Haff, 1991;Nalpanis et al, 1993;Greeley et al, 1996;Zou et al, 2001;Dong et al, 2002;Namikas, 2003;Dong et al, 2004;Huang et al, 2006;Cheng et al, 2006). Haff (1988, 1991) used a Gaussian distribution for the rebound velocity of particles and an exponential function for the ejected velocity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to deduce the sand velocity from the photographic images at very low heights where the grains are too crowded (e.g., Zou et al, 2001). Similarly, the selection of particles is inevitably subjective, and the number of detected particles is usually very limited and insufficient for detailed analysis of particle velocity in a blowing sand cloud (Dong et al, 2002a). The analysis of particle mean velocity, probability distribution of particle velocity, particle velocity fluctuation and particle turbulence requires measuring a sufficient number of sand particles.…”
Section: Introductionmentioning
confidence: 99%